Validation of a host blood transcriptomic biomarker for pulmonary tuberculosis in people living with HIV: a prospective diagnostic and prognostic accuracy study. Issue 6 (June 2021) - Mendelsohn, Simon C; Fiore-Gartland, Andrew; Penn-Nicholson, Adam; Mulenga, Humphrey; Mbandi, Stanley Kimbung; Borate, Bhavesh; Hadley, Katie; Hikuam, Chris; Musvosvi, Munyaradzi; Bilek, Nicole; Erasmus, Mzwandile; Jaxa, Lungisa; et al.
Summary: Background: A rapid, blood-based triage test that allows targeted investigation for tuberculosis at the point of care could shorten the time to tuberculosis treatment and reduce mortality. We aimed to test the performance of a host blood transcriptomic signature (RISK11) in diagnosing tuberculosis and predicting progression to active pulmonary disease (prognosis) in people with HIV in a community setting. Methods: In this prospective diagnostic and prognostic accuracy study, adults (aged 18–59 years) with HIV were recruited from five communities in South Africa. Individuals with a history of tuberculosis or household exposure to multidrug-resistant tuberculosis within the past 3 years, comorbid risk factors for tuberculosis, or any condition that would interfere with the study were excluded. RISK11 status was assessed at baseline by real-time PCR; participants and study staff were masked to the result. Participants underwent active surveillance for microbiologically confirmed tuberculosis by providing spontaneously expectorated sputum samples at baseline, if symptomatic during 15 months of follow-up, and at 15 months (the end of the study). The coprimary outcomes were the prevalence and cumulative incidence of tuberculosis disease confirmed by a positive Xpert MTB/RIF, Xpert Ultra, or Mycobacteria Growth Indicator Tube culture, or a combination of such, on at least two separate sputum samples collected within any 30-day period. Findings: Between March 22, 2017, and May 15, 2018, 963 participants were assessed for eligibility and 861 were enrolled. Among 820 participants with valid RISK11 results, eight (1%) had prevalent tuberculosis at baseline: seven (2·5%; 95% CI 1·2–5·0) of 285 RISK11-positive participants and one (0·2%; 0·0–1·1) of 535 RISK11-negative participants. The relative risk (RR) of prevalent tuberculosis was 13·1 times (95% CI 2·1–81·6) greater in RISK11-positive participants than in RISK11-negative participants. RISK11 had a diagnostic area under the receiver operating characteristic curve (AUC) of 88·2% (95% CI 77·6–96·7), and a sensitivity of 87·5% (58·3–100·0) and specificity of 65·8% (62·5–69·0) at a predefined score threshold (60%). Of those with RISK11 results, eight had primary endpoint incident tuberculosis during 15 months of follow-up. Tuberculosis incidence was 2·5 per 100 person-years (95% CI 0·7–4·4) in the RISK11-positive group and 0·2 per 100 person-years (0·0–0·5) in the RISK11-negative group. The probability of primary endpoint incident tuberculosis was greater in the RISK11-positive group than in the RISK11-negative group (cumulative incidence ratio 16·0 [95% CI 2·0–129·5]). RISK11 had a prognostic AUC of 80·0% (95% CI 70·6–86·9), and a sensitivity of 88·6% (43·5–98·7) and a specificity of 68·9% (65·3–72·3) for incident tuberculosis at the 60% threshold. Interpretation: RISK11 identified prevalent tuberculosis and predicted risk of progression to incident tuberculosis within 15 months in ambulant people living with HIV. RISK11's performance approached, but did not meet, WHO's target product profile benchmarks for screening and prognostic tests for tuberculosis. Funding: Bill & Melinda Gates Foundation and the South African Medical Research Council.